Use of Abandoned Solution-Mined Cavities for Storage of Plant Wastes - Charles H. Jacoby (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
A decision was made by the management of International Salt Co. in 1960 to eliminate all waste products which were entering the waters of Lake Seneca. This was to be accomplished by the injection of waste slurries into an abandoned brine cavity. The effluent from the cavity was to be treated and used for the manufacture of salt or disposed by deep well injection into the Cherry Valley limestone. After several years of research and design, a construction permit was granted by the state of New York; the injection, recovery, and disposal wells were constructed and after a public hearing an operational permit was issued. A summary of the operational results of the system is given.